2012
DOI: 10.1111/j.1464-5491.2012.03697.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical characteristics of diabetic peripheral neuropathy in hospital patients with Type 2 diabetes in Korea

Abstract: There was a high prevalence of peripheral neuropathy in patients with Type 2 diabetes in Korea and those patients were far more likely to have complications or co-morbidities. The proper management of diabetic peripheral neuropathy deserves attention from clinicians to ensure better management of diabetes in Korea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 28 publications
7
74
2
Order By: Relevance
“…According to findings of the Diabetic Neuropathy Study Group of the KDA, the actual prevalence of DPN is 33.5% ( n =1,338, study population=3,999) (Fig. 1) [11]. In the prior studies by that group, diagnostic criteria included the presence of documented DPN by quantitative sensory or nerve conduction studies, the presence of symptoms typically attributable to DPN after the exclusion of other causes of neuropathy, results from the Michigan Neuropathy Screening Instrument (MNSI, ≥3 score), and abnormal results on the 10 g monofilament test (2 out of 10).…”
Section: Prevalence Of Dpn In Koreamentioning
confidence: 99%
See 2 more Smart Citations
“…According to findings of the Diabetic Neuropathy Study Group of the KDA, the actual prevalence of DPN is 33.5% ( n =1,338, study population=3,999) (Fig. 1) [11]. In the prior studies by that group, diagnostic criteria included the presence of documented DPN by quantitative sensory or nerve conduction studies, the presence of symptoms typically attributable to DPN after the exclusion of other causes of neuropathy, results from the Michigan Neuropathy Screening Instrument (MNSI, ≥3 score), and abnormal results on the 10 g monofilament test (2 out of 10).…”
Section: Prevalence Of Dpn In Koreamentioning
confidence: 99%
“…A multivariate logistic regression analysis in patients with T2DM revealed that the clinical variables independently associated with DPN include older age, being female, a longer diabetes duration, lower hemoglobin A1c (HbA1c) level, the presence of retinopathy, a history of cerebrovascular accident, or peripheral arterial disease, the presence of hypertension or dyslipidemia, treatment with an oral hypoglycemic agent or insulin, and a history of foot ulcers (Fig. 2) [11]. As expected, patients identified in this study with painful DPN were older, typically female, had a longer duration of diabetes, showed more prevalent insulin use, and exhibited a greater incidence of other microvascular complications (retinopathy, nephropathy, or both) and hypertension compared to patients with nonpainful DPN [13].…”
Section: Clinical Characteristics Of Patients With Dpnmentioning
confidence: 99%
See 1 more Smart Citation
“…For older patients with diabetes duration greater than 25 years, about half have comorbid DPN and this can be associated with functional impairment and decreased quality of life (22). Factors associated with increased risk of DPN among the elderly with diabetes include female sex, longer duration of diabetes, retinopathy, stroke, hypertension, dyslipidemia, and a history of foot ulcers (23). …”
Section: Microvascularmentioning
confidence: 99%
“…This problem is associated with a number of elements that include axonal atrophy, demyelination, blunted regenerative potential, and loss of peripheral nerve fibers (4) . Some of the risk factors associated with diabetic neuropathy are age, female sex, diabetes duration, lower glycated haemoglobin, treatment with oral hypoglycaemic agents or insulin, presence of retinopathy, history of cerebrovascular or peripheral arterial disease, presence of hypertension or dyslipidaemia, and history of foot ulcer (5) .…”
Section: Introductionmentioning
confidence: 99%